The Effect of Infant Massage on The Quality of Sleep of Infants Aged 0–12 Months - Manurung, Rostinah (Universitas Aisyah Pringsewu, 2020)
Baby massage is one of the non-pharmacological therapies given to help improve the quality of sleep-in infants by means of baby massage. Baby massage is better done by the baby's parents. Babies who are massaged for approximately 15 minutes will feel more relaxed, sleep more soundly, their development and growth will be better. This study aims to analyze the effect of giving baby massage to the sleep quality of infants aged 0-12 months at Imelda Indonesian Workers General Hospital Medan 2020. The type of research used is a pre-experimental design with the One Group Pre-Test – Post Test approach. The population in this study were all infants in the General Hospital Imelda Indonesian Workers Medan. The sampling used is non-probability sampling with the sampling technique in this study is Accidental Sampling with a total sample of 30 infants. The independent variable is infant massage, and the dependent variable is the sleep quality of infants aged 0 -12 months. The research instrument used a questionnaire. Data processing using the Wilcoxon test. The results showed that the sleep quality of infants aged 0-12 months before the massage was mostly adequate for 17 respondents (56.7%) and after the massage, most of the respondents had good sleep quality as many as 20 respondents (66, 7%). Statistical test results show p-value is 0.000 0.05, so H1 is accepted. The conclusion of this study shows that H1 is accepted and H0 is rejected, which means that there is an effect of giving baby massage to the sleep quality of infants aged 0-12 months at the Imelda general hospital for Indonesian workers in Medan in 2020.